Formation mechanism of plateau, rapid fall and tail in phosphorus diffusion profile in silicon based on the pair diffusion models of vacancy mechanism and interstitial mechanism - Yoshida, Masayuki; Morooka, Masami; Tanaka, Shuji; Takahashi, Manabu (Diffusion Fundamentals, 2005)
P diffuses predominantly by the interstitial mechanism in Si. Assuming that there is a strong binding energy between P and I, therefore, the basic process of P diffusion is the diffusion of (PI), where I and (PI) represent self-interstitials and P-I pairs, respectively. In the high-P-concentration region, excess I is generated by the dissociation of (PI) and the limiting process of P diffusion depends on whether or not excess I is controlled. That is, if the concentration of excess I decreases relatively to the equilibrium I concentration due to the effect of the decrease in quasi self-interstitial formation energy, or if excess I is removed by the recombination with vacancies, P diffuses fast and the plateau is formed; if not, P diffuses slowly and the rapid fall is formed. In the tail region, the P concentration is low and the limiting process of P diffusion is the basic process of P diffusion, that is, the diffusion of (PI). Excess I generated in the high-P-concentration region diffuses into the low-P-concentration region, and I is supersaturated there. Therefore, the concentration of (PI) increases, resulting in the fast diffusion of P and the formation of the tail.